Sleep and the Pharmacotherapy of Alcohol Use Disorder: Unfortunate Bedfellows. A Systematic Review With Meta-Analysis - Panin, Francesca; Peana, Alessandra T. (Frontiers in Pharmacology, 2019)
Background: Sleep disorders are commonly associated with acute and chronic use of alcohol, and with abstinence. To date, there are four approved drugs to treat Alcohol Use Disorder (AUD): disulfiram, acamprosate, naltrexone and nalmefene. These AUD therapies reduce the craving and risk of relapse into heavy drinking, but little is known about their effect on sleep. As recent evidences indicate a crucial role of sleep disorders in AUD, claiming that sleep problems may trigger alcohol abuse and relapses, it is fundamental to clarify the impact of those drugs on the sleep quality of AUD patients. This systematic review aims to answer the question: how does the pharmacotherapy for AUD affect sleep? Methods: We searched PubMed, EMBASE, CINAHL plus, Cochrane and SCOPUS using sleep- and AUD pharmacotherapy- related keywords. The articles included were appraised using the CASP checklists and the risk of bias was assessed following the Cochrane Risk of Bias assessment tool. Finally, we pooled sleep outcomes in a meta-analysis to measure the overall effect. Results and conclusion: We included 26 studies: only three studies focused on sleep as a main outcome, two with polysomnography (objective measurement) and one with subjective self-reported sleep, while all the other studies reported sleep problems among the adverse effects (subjective report). The only study available on disulfiram showed reduced REM sleep. Acamprosate showed no/little effect on self-reported sleep, but improved sleep continuity and architecture measured by polysomnography. The two opioidergic drugs naltrexone and nalmefene had mainly detrimental effect on sleep, giving increased insomnia and/or somnolence compared with placebo, although not always significant. The meta-analysis confirmed significantly increased somnolence and insomnia in the naltrexone group, compared with the placebo. Overall, the currently available evidences show more sleep problems with the opioidergic drugs (especially naltrexone), while acamprosate seems to be well tolerated or even beneficial. Acamprosate might be a more suitable choice when patients with AUD report sleep problems. Due to the paucity of information available, and with the majority of results being subjective, more research on this topic is needed to further inform the clinical practice, ideally with more objective measurements such as polysomnography.